Melittin enables efficient vesicular escape and enhanced nuclear access of nonviral gene delivery vectors - Ogris, M; Carlisle, RC; Bettinger, T; Seymour, LW (American Society for Biochemistry and Molecular Biology, 2001)
Entry of exogenously applied DNA into the cytoplasm and subsequent transport into the nucleus are major cellular barriers for nonviral gene delivery vectors. To overcome these barriers, we have covalently attached the cationic peptide melittin to poly(ethylenimine) (PEI). This conjugate condensed DNA into small, discrete particles (<100 nm in diameter), and the membrane lytic activity of melittin enabled efficient release of the DNA into the cytoplasm, as monitored by fluorescence microscopy and flow cytometry. Compared with PEI, the transfection activity was strongly increased within a broad range of cell lines and types tested, including different tumor cell lines but also primary hepatocytes and human umbilical vein endothelial cells. The early onset of gene expression (within 4 h, reaching maximal values after 12 h) and the high reporter gene expression achieved in slowly dividing or confluent cells suggested a further role of melittin after releasing the DNA into the cytoplasm. Intracytoplasmic microinjection of melittin-containing PEI·DNA complexes into fibroblasts produced 40% cellular frequency of reporter gene expression that was inhibitable by co-injection of wheat germ agglutinin, whereas simple PEI·DNA complexes showed only 10%. These data suggest that melittin enables release of nonviral gene transfer particles into the cytoplasm and also enhances their transport into the nucleus, possibly via the cationic cluster KRKR near the C terminus of the peptide.